Assessing Perception of Role Transition among Nurse Interns - Amina A. Abd Elfatah; Samia M. Adam; Hanaa M. Abrabu; Galila M. Abd Elghafar (Evidence-Based Nursing Research)
Context: Nursing roles today constitute a vast and complex system. Nurse interns need to know their future roles to facilitate and prepare them socially to work professionally and decrease the reality shock when going outside to the labor market.